Effects of nonprotein nitrogen source in blocks on intake and digestion of prairie hay by steers - C.A. Löest; James S. Drouillard; B.D. Lambert; A.M. Trater; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2000)
This intake and digestion study evaluated source of nonprotein nitrogen in cooked molasses blocks supplemented to 18 steers (590 lb) with ad libitum access to prairie hay, Treatments were 1) control (no block), 2) a block containing 60% crude protein with 83% from urea (UREA block), and 3) a block containing 60% crude protein with 42% from urea and 42% from biuret (UREA/BIURET block). Blocks were broken into small pieces to facilitate rapid consumption and fed once daily at .125% of body weight. Forage intake increased by 22%, total intakes (forage plus block) increased by 28%, and digestible organic matter intakes increased by 52% when either UREA or UREA/BIURET blocks were fed. Total diet digestibilities also increased with block supplementation. Intakes and digestibilities were similar for the UREA and UREA/BIURET blocks. Supplementing prairie hay with cooked molasses blocks containing high levels of nonprotein nitrogen increased intake and digestion, but replacing half of the urea with biuret had little effect.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Steers; Forages; Urea; Biuret